Usability Assessment of E-commerce Portal Using Agent Framework - Prasad, KDV (The journal of contemporary issues in business and government, 2023)
It’s commonly known that evaluating e-commerce websites’ usability is essential, and researchers have devoted a lot of time and resources to it over the previous decade. Commerce has increased dramatically as e-retailers interact with clients online. They expect a great user experience in addition to exceptional products and services. The user experience is influenced by branding, functionality, navigation, content, aesthetics, and usability. This study examines usability assessment of e-commerce portal using agent framework.